The effect of flap thickness on corneal biomechanics after myopic laser in situ keratomileusis using the M-2 microkeratome - Goussous IA (Dove Medical Press, 2017)
Iyad A Goussous,1 Mohamed-Sameh El-Agha,1 Ahmed Awadein,1 Mohamed H Hosny,1 Alaa A Ghaith,2 Ahmed L Khattab2 1Department of Ophthalmology, Faculty of Medicine, Cairo University, Cairo, 2Faculty of Medicine, Alexandria University, Alexandria, Egypt Purpose: The purpose of this study was to determine the effect of flap thickness on corneal biomechanics after myopic laser in situ keratomileusis (LASIK).Methods: This is a prospective controlled non-randomized, institutional study. Patients underwent either epi-LASIK with mitomycin (advanced surface ablation [ASA]), thin-flap LASIK (90 µm head), or thick-flap LASIK (130 µm head). In ASA, the Moria Epi-K hydroseparator was used. LASIK flaps were created using the Moria M-2 mechanical microkeratome. The corneal hysteresis (CH) and corneal resistance factor (CRF) were measured preoperatively and 3 months after surgery, using the Ocular Response Analyzer®.Results: Ten patients (19 eyes) underwent ASA, 11 patients (16 eyes) underwent thin-flap LASIK, and 11 patients (16 eyes) underwent thick-flap LASIK. The mean preoperative CH was 10.47±0.88, 10.52±1.4, and 11.28±1.4 mmHg (p=0.043), respectively, decreasing after surgery by 1.75±1.02, 1.66±1.00, and 2.62±1.03 mmHg (p=0.017). The mean reduction of CH per micron of central corneal ablation was 0.031, 0.023, and 0.049 mmHg/µm (p=0.005). Mean preoperative CRF was 10.11±1.28, 10.34±1.87, and 10.62±1.76 mmHg (p=0.66), decreasing after surgery by 2.33±1.35, 2.77±1.03, and 2.92±1.10 mmHg (p=0.308). The mean reduction of CRF per micron of central corneal ablation was 0.039, 0.040, and 0.051 mmHg/µm (p=0.112).Conclusion: Thick-flap LASIK caused a greater reduction of CH and CRF than thin-flap LASIK and ASA, although this was statistically significant only for CH. ASA and thin-flap LASIK were found to be biomechanically similar. Keywords: flap thickness ectasia, hysteresis, LASIK, surface ablation